Differentiation between checks to the head or neck as a primary cause of mild traumatic brain injury in ice hockey in Slovakia - Parnican, S.; Peracek, P.; Toth, I. (Journal of Physical Education and Sport, 2020)
The objective of the research was to deepen and expand the knowledge about checks to the head or neck in Slovak ice hockey,and its differentiation. Our source of information was the pedagogical practice itself; various regular season games across four ice hockey leagues in the 2019/2020 season in Slovakia.However, considering the safety and protective measures due to the COVID-19 pandemic, the season was terminated prematurely.We conducted an indirect observation of the ice hockey games recorded on data storage available in the records of the Slovak ice hockey federation. We recorded 81 incidences of checks to the head or neck in 1,297 games.To prove the statistical significance, we used the z-score test for 2 proportions (p=0.01). We showed that the zone where the majority of head or neck checks occuris the area along the boards (zone 1) with a relative value of 59.26% (p<0.01).The playingposition of forward (67.90%) has proven to be significantly the most risky for being checked to the head or neck (p<0.01). Ultimately, we confirmed an assumption, that checking to the head or neck will most commonly happen just prior to or right after receiving a pass, or while passing or shooting the puck. A statistically significant majority of incidences of head or neck checksoccurred up to two seconds after the checked player received the puck (p<0.01). In 20.99% ofhead or neck checks, the checked player wasn`t in control of the puck. In comparison to other researches (Hutchison, Comper, Meeuwisse and Echemendia 2015a, 2015b; Kuhn and Solomon 2015 etc.) aimed at National Hockey League(NHL) or Collegiate ice hockey leagues in North America, despite the differences in the ice hockey rink dimensions, the level of the game performance of the teams and players and the number of one-on-one battles, we are stating a similar proportion of observed variables. According to the obtained data, we recommend the progressive development of visual perception through an increase of the frequency of the utilization of game-based drills and small-sided games with modified rules and the highest possible number of one-on-one battles in training practice. It is necessary to require an absolute overview (game sense)of a game from players, an associative solution along with a productive solution of the game situation. We also recommend an interdisciplinary cooperation of competent scientific disciplinesin an effort to detect new knowledge and information on this topic.